Chronic right lower abdominal quadrant pain and the vermiform appendix - Sukumaran, Vengayil; Teli, Bhavuray; Avula, Sreekant; Pavuluru, Jagadeesh; Arakeri, Satish (International Surgery Journal, 2016)
Background: Although chronic right lower quadrant (RLQ) abdominal pain is a common clinical condition, the diagnosis and treatment is still under debate. In spite of literature evidence, existence of recurrent or chronic appendicitis continues to be debated-especially, whether chronic appendicitis really exists and whether it can explain the persistent or chronic right lower quadrant abdominal pain. We study here whether undiagnosed chronic RLQ abdominal pain can be due to appendix and whether it will be relieved after elective laparoscopic appendicectomy. In literature there are quite a few studies on this, but all are limited by smaller sample size. Methods: 200 patients, 12-60 years of age, with undiagnosed chronic RLQ abdominal pain underwent diagnostic laparoscopy and appendicectomy. Twenty patients were excluded from the final analysis because of the presence of an obvious non-appendicular pathology also. Patients were followed up for 6 months at regular intervals (one, three and six month) and were assessed for pain relief. The association between clinical outcome and histopathological outcome was studied. Results: The histopathological examination of appendices revealed appendicitis in all patients. Intra-operative evidences of chronic appendicitis were seen in 160 (88.8%) patients. 175 (97.2%) patients were completely pain free on follow up and only 5 (2.8%) patients had persistence of pain. Conclusions: Patients with chronic RLQ abdominal pain (without obvious diagnosis on preoperative evaluation) can safely undergo exploratory laparoscopy and appendicectomy. Chronic appendicitis is a diagnosis of exclusion with intra-operative and histopathological evidence. Patients with RLQ abdominal pain and right iliac fossa (RIF) tenderness with otherwise normal findings on sonology are having chronic or recurrent inflammation of the vermiform appendix and are fully curable by laparoscopic appendicectomy.